Discrepant NOXA (PMAIP1) transcript and NOXA protein levels: a potential Achilles' heel in mantle cell lymphoma - Dengler, M A (Nature Publishing Group, 2014)
Mantle cell lymphoma (MCL) is an aggressive lymphoid neoplasm with transient response to conventional chemotherapy. We here investigated the role of the Bcl-2 homology domain 3-only protein NOXA for life–death decision in MCL. Surprisingly, NOXA (PMAIP1) mRNA and NOXA protein levels were extremely discrepant in MCL cells: NOXA mRNA was found to be highly expressed whereas NOXA protein levels were low. Chronic active B-cell receptor signaling and to a minor degree cyclin D1 overexpression contributed to high NOXA mRNA expression levels in MCL cells. The phoshatidyl-inositol-3 kinase/AKT/mammalian target of rapamycin pathway was identified as the major downstream signaling pathway involved in the maintenance of NOXA gene expression. Interestingly, MCL cells adapt to this constitutive pro-apoptotic signal by extensive ubiquitination and rapid proteasomal degradation of NOXA protein (T(½)∼15–30 min). In addition to the proteasome inhibitor Bortezomib, we identified the neddylation inhibitor MLN4924 and the fatty acid synthase inhibitor Orlistat as potent inducers of NOXA protein expression leading to apoptosis in MCL. All inhibitors targeted NOXA protein turnover. In contrast to Bortezomib, MLN4924 and Orlistat interfered with the ubiquitination process of NOXA protein thereby offering new strategies to kill Bortezomib-resistant MCL cells. Our data, therefore, highlight a critical role of NOXA in the balance between life and death in MCL. The discrepancy between NOXA transcript and protein levels is essential for sensitivity of MCL to ubiquitin-proteasome system inhibitors and could therefore provide a druggable Achilles' heel of MCL cells.